Embodied Conceptual Combination - Lynott, Dermot; Connell, Louise (Frontiers in Psychology, 2010)
Conceptual combination research investigates the processes involved in creating new meaning from old referents. It is therefore essential that embodied theories of cognition are able to explain this constructive ability and predict the resultant behaviour. However, by failing to take an embodied or grounded view of the conceptual system, existing theories of conceptual combination cannot account for the role of perceptual, motor and affective information in conceptual combination. In the present paper, we propose the Embodied Conceptual Combination (ECCo) model to address this oversight. In ECCo, conceptual combination is the result of the interaction of the linguistic and simulation systems, such that linguistic distributional information guides or facilitates the combination process, but the new concept is fundamentally a situated, simulated entity. So, for example, a cactus beetle is represented as a multimodal simulation that includes visual (e.g., the shiny appearance of a beetle) and haptic (e.g., the prickliness of the cactus) information, all situated in the broader location of a desert environment under a hot sun, and with (at least for some people) an element of creepy-crawly revulsion. The ECCo theory differentiates interpretations according to whether the constituent concepts are destructively, or nondestructively, combined in the situated simulation. We compare ECCo to other theories of conceptual combination, and discuss how it accounts for classic effects in the literature.